Bridging the Gap between Knowing and Modeling Viruses in Marine Systems—An Upcoming Frontier - Mateus, Marcos D. (Frontiers in Marine Science, 2017)
Viruses are the most abundant biological entities in the world's oceans. Their potential control on phytoplankton and bacterioplankton dynamics and diversity, and consequent effect on the flow of energy and matter in food webs, is now beyond dispute. Paradoxically, their importance seems to be persistently underestimated by marine modelers, frequently by exclusion, despite the uninterrupted volume of knowledge advanced during the past decades. Bridging the gap between knowing and modelling the role of viruses is, undoubtedly, one of the upcoming frontiers to be crossed in modelling the plankton. This paper has a two-fold objective: (1) review the knowledge on the roles of viruses in marine systems that has been put forward over the past decades, and (2) see how viruses have been incorporated into marine ecosystem models.